Salivary tissue factor concentration and activity in patients with oral lichen planus - (:unkn) unknown (ELSEVIER SCI LTD, 2017)
Purpose: This study aimed to evaluate the tissue factor (TF) concentration and activity in patients with oral lichen planus (OLP) under oxidative stress. Methods: Twenty patients with OLP were selected from the patients who were referred for treatment to the Marmara University, Faculty of Dentistry, Oral and Maxillofacial Radiology Department. Twenty healthy subjects from faculty staff and their family members were selected for the study. Salivary TF concentration and TF activity; total oxidant capacity; total antioxidant capacity; total thiol, malondialdehyde and glutathione concentrations; and oxidative stress index were measured in saliva samples. Results: Salivary total oxidant capacity, oxidative stress index and malondialdehyde and TF concentration and activity were significantly increased in the patient group compared to those in the control group. Total thiol and glutathione concentration and total antioxidant capacity were significantly decreased in the patient group. Conclusion: Impaired oxidant-antioxidant balance and inflammatory features of OLP might cause an increase in the salivary TF concentration and activity. As TF factor plays a critical role in inflammation progress, the use of an antioxidant agent in OLP may decrease the salivary TF concentration by decreasing oxidative stress. The findings of this study might represent a novel approach to OLP monitoring and treatment in terms of TF as the measurement of TF is easy and cost-effective. (C) 2016 Published by Elsevier Ltd on behalf of Japanese Stomatological Society.
Keywords: Oral lichen planus; Tissue factor; Oxidative stress; Saliva; OXIDATIVE STRESS; ANTIPHOSPHOLIPID ANTIBODIES; LIPID-PEROXIDATION; CANCER PROGRESSION; INFLAMMATION; BLOOD; SERUM; EXPRESSION; MARKERS